Variation in microbial CAZyme families across degradation severity in a steppe grassland in northern China - Zhang, Qian; Xu, Xiaoqing; Duan, Junguang; Koide, Roger T.; Xu, Lei; Chu, Jianmin (Frontiers in Environmental Science, 2023)
Grassland degradation reduces soil carbon sequestration capacity and enhances soil carbon loss, but little is known about the mechanisms involved, including changes in the CAZy genes responsible for C cycling. Here we used a metagenomic approach to reveal variation in abundance and composition of CAZy genes in grasslands experiencing a range of degradation severity (i.e., non-, light, moderately and severely degraded) in two soil layers (0-10cm,10-20cm) in a grassland in northern China. Both degradation severity and soil depth significantly affected CAZy gene abundance. CAZy abundance was higher in the severely degraded grassland than in the other three degradation severities. Indicator species analysis showed that the severely degraded grassland was enriched in CAZy genes. Glycoside hydrolases (GH) and glycosyltransferases (GT) were the two most abundant gene families. The Mantel test and variation partitioning suggested an interactive effect degradation severity and soil depth in affecting CAZy gene composition. Structural equation modelling identified soil total carbon, organic carbon and microbial biomass carbon as the three most important soil characteristics, which suggests an interaction between degradation severity and these soil variables in the determination of of CAZy gene composition. This suggests that both above- and belowground factors linked to soil organic matter play a central role in determining the abundance of CAZy gene families. For example, the high abundance of CAZy gene families in severely degraded grassland suggests that low productivity and low litter input stimulates consumption by microorganisms, resulting in poor C sequestration and enhancing C loss. Thus, our results imply that conventional strategies employing grazing exclosures for mitigating degradation are unlikely to prevent C loss without anthropogenic intervention to improve productivity in the severely degraded grassland.